The Effectiveness of Cooperative Learning Type Take and Give Learning (TGL) on Discussion Skills to Support the Formation of the Pancasila Student Profile among Fifth Grade Students of SD Santo Yoseph Denpasar - Maximiliana Ni Made Pinko Sri Handayani; Krisma Widi Wardani (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to examine the effectiveness of the Take and Give Learning (TGL) model in improving students’ discussion skills to support the development of the Pancasila Student Profile. The research employed an experimental method, with data collected through observation, assessment rubrics, documentation, pretests, and posttests. The instruments used were tested for validity and reliability (α = 0.88). The Mann-Whitney test results showed a significant difference between the experimental and control groups (Asymp. Sig. = 0.000), with the experimental group having a higher post-test mean score (30.33). The implementation of the TGL model proved effective in enhancing students’ discussion skills. In addition, this model reinforced the eight dimensions of the Pancasila Student Profile, including faith in and devotion to God Almighty and noble character, independence, critical thinking skills, creativity, collaboration, appreciation of diversity in a global context, communicative abilities, as well as a commitment to shared prosperity and environmental sustainability.